2020
DOI: 10.1139/cjfr-2018-0508
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying forest loss and forest degradation in Myanmar’s “home of teak”

Abstract: The Bago Mountain Range in Myanmar is known as the “home of teak” (Tectona grandis L. f.) because of its bountiful, naturally growing teak-bearing forests. Accelerating forest loss and degradation are threatening the sustainable production of teak in the region. Changes in land cover between 2000 and 2017 in four reserved forests of the Bago Mountain Range were mapped using supervised classification of Landsat imagery and training data collected in the field. A stratified random sample was used to collect refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Thailand produced approximately 71,954.53 m 3 of teak plantation timber and exported wood products worth 1.1 billion baht overseas in 2018, according to the Forest Industry Organization (FIO) [14]. However, teak logs produced from natural teak forests are declining due to illegal logging, over-cutting, deforestation, and land-use changes [3,4,9,10]. Since 1953, there has been a 94% decline in Thailand's important natural teak forests [11].…”
Section: Introductionmentioning
confidence: 99%
“…Thailand produced approximately 71,954.53 m 3 of teak plantation timber and exported wood products worth 1.1 billion baht overseas in 2018, according to the Forest Industry Organization (FIO) [14]. However, teak logs produced from natural teak forests are declining due to illegal logging, over-cutting, deforestation, and land-use changes [3,4,9,10]. Since 1953, there has been a 94% decline in Thailand's important natural teak forests [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, the global teakwood supply from the natural teak forests has been dwindling since the early 21 st century (FAO, 2009;Pandey and Brown, 2000). It has Wood Physical and Mechanical Properties of Clonal Teak (Tectona grandis) Stands Under Different Thinning and Pruning Intensity Levels Planted in Java, Indonesia also been forecasted that the natural teak forests will not be able to sustainably meet the demand for teakwood in the global market due to some critical environmental issues (FAO, 2015;Kyaw et al, 2020;Mon et al, 2012). However, teak plantations have a good prospect of sustainably supplying teak timber in the global market since the cultivation has been successfully established in 65 countries outside its natural distribution (Koskela et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The Bago Yoma region in Myanmar was once regarded as the 'home of teak' (Kermode 1964). However, changes in land cover between 2000 and in four reserved forests of the Bago mountain range showed that forest area declined from 71,240 ha in 2000 to 40,891 ha in 2017, and the area of degraded forests increased from 88,797 ha to 97,013 ha (Kyaw et al 2020). In consideration of the current teak forests and quality, it is important to emphasize the role of tree improvement and genetic resource conservation in Myanmar.…”
Section: Introductionmentioning
confidence: 99%